Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\frac{-3}{5}.\left(\frac{5}{7}+\frac{3}{7}+\frac{6}{7}\right)\)
=\(\frac{-3}{5}.\)\(\frac{14}{7}\)
=\(-\frac{3}{5}.2\)
=-6/5
Câu 1:
\(S=\frac{10}{7}+\frac{10}{7^2}+\frac{10}{7^3}+...+\frac{10}{7^{10}}\)
\(\frac{1}{7}S=\frac{10}{7^2}+\frac{10}{7^3}+....+\frac{10}{7^{11}}\)
\(\rightarrow\)\(\left(1-\frac{1}{7}\right).S=\frac{10}{7}-\frac{10}{7^{11}}\)
=> \(S=\frac{10.7^{10}-10}{7^{10}.6}\)
Tính hợp lý
\(\frac{-5}{7}\). \(\frac{6}{19}\)+ \(\frac{13}{-7}\). \(\frac{5}{19}\)- \(\frac{15}{7}\)
\(\frac{-5}{7}.\frac{6}{19}+\frac{13}{-7}.\frac{5}{19}-\frac{15}{7}=\frac{-5}{7}.\frac{6}{19}+\frac{13}{19}.\frac{-5}{7}+\frac{-5}{7}.3\)
\(=\frac{-5}{7}.\left(\frac{6}{19}+\frac{13}{19}+3\right)=\frac{-5}{7}.4=\frac{-20}{7}\)
\(x-40\%x=3,6\)
\(\Rightarrow100\%x-40\%x=3,6\)
\(\Rightarrow60\%x=3,6\)
\(\Rightarrow\frac{60}{100}x=3,6\)
\(\Rightarrow x=6\)
\(3\frac{2}{7}x-\frac{1}{3}=-2\frac{3}{4}\)
\(\Rightarrow\frac{23}{7}x-\frac{1}{3}=-\frac{11}{4}\)
\(\Rightarrow\frac{23}{7}x=-\frac{33}{12}+\frac{4}{12}\)
\(\Rightarrow\frac{23}{7}x=\frac{29}{12}\)
\(\Rightarrow x=\frac{29}{12}:\frac{23}{7}=\frac{203}{276}\)
(x+1/4-1/3).(13/6-1/4)=7/46
(x+1/4-1/3).23/12=7/46
(x+1/4-1/3)=7/46:23/12
(x+1/4-1/3)=7/46.12/23
(x+1/4-1/3)=42/529
x+1/4=42/529+1/3
x+1/4=655/1587
x=655/1587-1/4
x=1033=/6348
vậy x=1033/6348
a) => 4/3x = 7/9 - 4/9 = 1/3
=> x = 1/3 : 4/3 = 1/4
b) => 5/2 - x = 9/14 : (-4/7) = -9/8
=> x = 5/2 - (-9/8) = 5/2 + 9/8 = 29/8
c) => 3x = 2 và 2/3 - 3/4 = 8/3 - 3/4 = 23/12
=> x = 23/12 : 3 = 23/36
D) => -5/6 - x = 1/4
=> x = -5/6 - 1/4 = -13/12
a) \(\dfrac{4}{9}+\dfrac{4}{3}x=\dfrac{7}{9}\)
\(\dfrac{4}{3}x=\dfrac{7}{9}-\dfrac{4}{9}=\dfrac{1}{3}\)
\(x=\dfrac{1}{3}:\dfrac{4}{3}\)
\(x=\dfrac{1}{4}\)
b) \(\left(\dfrac{5}{2}-x\right)\left(-\dfrac{4}{7}\right)=\dfrac{9}{14}\)
\(\dfrac{5}{2}-x=\dfrac{9}{14}:\left(-\dfrac{4}{7}\right)=-\dfrac{9}{8}\)
\(x=\dfrac{5}{2}-\left(-\dfrac{9}{8}\right)\)
\(x=\dfrac{29}{8}\)
c) \(3x+\dfrac{3}{4}=2\dfrac{2}{3}\)
\(3x+\dfrac{3}{4}=\dfrac{8}{3}\)
\(3x=\dfrac{8}{3}-\dfrac{3}{4}=\dfrac{23}{12}\)
\(x=\dfrac{23}{12}:3\)
\(x=\dfrac{23}{36}\)
d) \(-\dfrac{5}{6}-x=\dfrac{7}{12}+\dfrac{-1}{3}\)
\(-\dfrac{5}{6}-x=\dfrac{1}{4}\)
\(x=-\dfrac{5}{6}-\dfrac{1}{4}\)
\(x=-\dfrac{13}{12}\)
a) Ta có: \(-x+\frac{4}{7}=\frac{1}{3}\)
\(\Leftrightarrow-x=-\frac{5}{21}\)
\(\Rightarrow x=\frac{5}{21}\)
b) Ta có: \(x\div\left(-\frac{1}{3}\right)^2=-\frac{1}{3}\)
\(\Rightarrow x=\left(-\frac{1}{3}\right)^3=-\frac{1}{27}\)
c) \(\left(\frac{3}{5}\right)^5.x=\left(\frac{3}{5}\right)^7\)
\(\Rightarrow x=\left(\frac{3}{5}\right)^2=\frac{9}{25}\)
\(a.-x+\frac{4}{7}=\frac{1}{3}\)
\(-x=\frac{1}{3}-\frac{4}{7} \)
\(-x=\frac{7}{21}-\frac{12}{21}\)
\(-x=\frac{-5}{21}\)
\(x=\frac{5}{21}\)
\(b.x:\left(\frac{-1}{3}\right)^2=\frac{-1}{3}\)
\(x=\frac{-1}{3}.\left(\frac{-1}{3}\right)^2\)
\(x=\frac{-1}{3}.\frac{-1}{3}.\frac{-1}{3}\)
\(x=\frac{-1}{27}\)
\(c.\left(\frac{3}{5}\right)^5.x=\left(\frac{3}{5}\right)^7\)
\(x=\left(\frac{3}{5}\right)^7:\left(\frac{3}{5}\right)^5\)
\(x=\left(\frac{3}{5}\right)^2\)
\(x=\frac{3}{5}.\frac{3}{5}\)
\(x=\frac{9}{25}\)
\(\frac{5}{6}.\frac{4}{19}+\frac{-7}{12}.\frac{4}{19}-\frac{40}{57}\)
\(=\frac{4}{19}.\left(\frac{5}{6}+\frac{-7}{12}\right)-\frac{40}{57}\)
\(=\frac{4}{19}.\frac{1}{4}-\frac{40}{57}\)
\(=\frac{1}{19}-\frac{40}{57}\)
\(=\frac{43}{57}\)